Partial depolymerization of genetically modified potato tuber periderm reveals intermolecular linkages in suberin polyester. (September 2015) - Graça, José; Cabral, Vanessa; Santos, Sara; Lamosa, Pedro; Serra, Olga; Molinas, Marisa; Schreiber, Lukas; Kauder, Friedrich; Franke, Rochus
Graphical abstract: Potato periderm suberin builds as a macromolecule from a glycerol – octadec-9-ene-1, 18-dioic acid – glycerol backbone, linked in its periphery to polyaromatics through the glycerol – 18-hydroxyoctadec-9-enoic acid – ferulic acid connection. Highlights: A model for the potato periderm suberin macromolecular arrangement is proposed. C18 α, ω-diacids esterified at both ends to glycerol is the core of suberin aliphatics. Ferulic acid is linked to the suberin aliphatics through linking to ω-hydroxyacids. The silencing of the ω-hydroxylase CYP86A33 -gene strongly affects suberin aliphatics. The silencing of the acyltransferase FHT -gene reduces ferulate esters in suberin. Abstract: Suberin is a biopolyester found in specialized plant tissues, both internal and external, with key frontier physiological functions. The information gathered so far from its monomer and oligomer composition, and in situ studies made by solid state techniques, haven't solved the enigma of how the suberin polyester is assembled as a macromolecule. To investigate how monomers are linked in suberin, we analyzed oligomer fragments solubilized by the partial depolymerization of suberin from potato ( Solanum tuberosum ) tuber periderms. The structure of the suberin oligomers, namely which monomers they included, and the type and frequency of the inter-monomer ester linkages, was assessed by ESI-MS/MS and high resolution NMR analysis. The analyzed potato periderms included the one from wild type (cv. Desirée) and from plants where suberin-biosynthesis genes were downregulated in chain elongation ( StKCS6 ), ω-hydroxylation ( CYP86A33 ) and feruloylation ( FHT ). Two building blocks were identified as possible key structures in the macromolecular development of the potato periderm suberin: glycerol – α, ω-diacid – glycerol, as the core of a continuous suberin aliphatic polyester; and glycerol – ω-hydroxyacid – ferulic acid, anchoring this polyaliphatic matrix at its periphery to the vicinal polyaromatics, through linking to ferulic acid. The silencing of the StKCS6 gene led to non-significant alterations in suberin structure, showing the relatively minor role of the very-long chain (>C28) fatty acids in potato suberin composition. The silencing of CYP86A33 gene impaired significantly suberin production and disrupted the biosynthesis of acylglycerol structures, proving the relevance of the latter and thus of the glycerol – α, ω-diacid – glycerol unit for the typical suberin lamellar organization. The silencing of the FHT gene led to a lower frequency of ferulate linkages in suberin polyester but to more polyphenolic guaiacyl units as seen by FTIR analyses in the intact polymer.